Facile electrodeposition of V-doped CoP on vertical graphene for efficient alkaline water electrolysis. Issue 22 (31st March 2020) - Truong, Linh; Roy, Sanjib Baran; Jerng, Sahng-Kyoon; Jeon, Jae Ho; Lee, Sunghun; Chun, Seung-Hyun
Abstract : In this work, we demonstrate a highly enhanced electrocatalytic activity of vanadium-doped CoP (V–CoP), directly grafted on a vertical graphene/carbon cloth electrode (VG/CC) by a facile electrochemical deposition method. Abstract : In this work, we demonstrate a highly enhanced electrocatalytic activity of vanadium-doped CoP (V–CoP), directly grafted on a vertical graphene/carbon cloth electrode (VG/CC) by a facile electrochemical deposition method. Impressively, V–CoP/VG/CC exhibited a superior catalytic activity toward the hydrogen evolution reaction (HER) in alkaline solution. Compared to CoP/VG/CC, V-doping decreased the overpotential for HER at 10 mA cm −2 by more than half to 40 mV. The new catalyst even outperformed Pt/C beyond 150 mA cm −2 . The overpotential for OER at 50 mA cm −2 was merely 314 mV, more than 100 mV lower than that of IrO2 . Moreover, our novel catalyst worked as an excellent bifunctional catalyst with a low cell voltage of 1.69 V to achieve a current density of 50 mA cm −2 . Detailed characterizations revealed that the V-doping in CoP resulted in improved electrical conductivity and increased active sites. Our findings highlight the significant advantage of V doping on the catalytic activities of CoP, already boosted by VG. Furthermore, concurrent doping with the electrodeposition of catalyst offers a new approach for practical water electrolysis.